Prevalence of depression among elderly population in rural South India - Vincent, Vivin; Shanmugam, Jeevithan; Duraisamy, Shanmugapriya; Loganathan, Padmavathy; Ganeshkumar, Vijay; Balakrishnan, Vedanayaki (International Journal Of Community Medicine And Public Health, 2020)
Background: Depression among elderly is the commonest psychiatric disorder however it is commonly misdiagnosed and under treated. Most of the time it is considered as part of aging process rather than a treatable condition. Diagnosing depression in the elderly is often difficult as a result of presence of cognitive impairment as well as reluctance and denial by the elderly and their family members. Objective of the study was to estimate the prevalence of depression among elderly rural population in South India. Methods: A community based cross sectional study was conducted over a period of 2 months among 575 elderly people aged 60 years and above in the rural field practice area of a tertiary care hospital in south India using a pre validated Geriatric Depression Scale. Data entered and analysed using MS Excel. Results: 77.56% of the study participants were found to be depressed. Among them 74.66% were mild depressive and 25.34% had severe depression. Depression was common in elderly males as compared to females. The prevalence of depression was higher in those who live single and those living with their children without their spouse and those with co morbidities. Conclusions: Prevalence of depression among elderly is high in rural areas. It also increases as the age increases. Early identification and timely intervention would promote healthy old age.